Peningkatan Kemandirian Anak Yatim melalui Pelatihan Keterampilan di Panti Asuhan Wisma Karya Bakti - Muhammad Faris Hermawan; Wa Ode Asmawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Losing parents at an early age has a negative impact on children's development, psychologically, emotionally and socially. Orphans often face great challenges in social problems so that they cannot prepare for an adequate future, with skills training aimed at empowering orphans for a more independent future. This study aims to determine the implementation of skills programs in increasing the independence of orphans in orphanages. The research method used is qualitative, with data coming from participants or orphans who take part in skills training at the Wisma Karya Bakti Orphanage and caregivers. The sample was taken using purposive technique as many as 7 people. Data collection techniques include observation, interviews, and documentation. Data analysis is carried out by a method that involves steps such as working with data, organizing, sorting, synthesizing, identifying patterns, finding relevant information, and determining important points. The results showed that the implementation of the skills program carried out by the Wisma Karya Bakti Orphanage is currently implementing 3 stages carried out from the awareness stage as the initial stage of orphans being made aware of the importance of having skills. Then the transformation of knowledge orphans are given some skills training. Then finally increasing the intellectual and skill proficiency of the orphans is given the opportunity to apply the skills that have been learned. The three stages in empowerment through skills help develop the potential that exists within orphans in increasing their independence.